Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery including same
By forming a high and low concentration cobalt coating on the surface of the positive electrode active material of the lithium-ion battery, the problem of easy structure damage in the charging and discharging process of the lithium-ion battery positive electrode material is solved, and high efficiency and long-life battery performance is achieved.
Patent Information
- Application Number
- JP2023089044
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-19
- Filing Date
- 2023-05-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-05-30
AI Technical Summary
The positive electrode active materials of existing lithium-ion batteries are easily damaged during charging and discharging, resulting in a shortened battery life, increased resistance and poor capacity performance.
A lithium nickel-based composite oxide positive electrode active material containing secondary particles and single particles is used, and a high- and low-concentration cobalt coating area is formed on its surface to improve the primary charge and discharge efficiency and life characteristics of the battery.
It realizes high capacity and high energy density of lithium-ion batteries, improves charging and discharging efficiency and battery life, and improves safety.
Smart Images

Figure 0007648679000007 
Figure 0007648679000008 
Figure 0007648679000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a method for producing the same, and a lithium secondary battery including the same. [Background technology]
[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage sources for hybrid and electric vehicles.
[0003] In order to realize a lithium secondary battery suitable for such applications, various positive electrode active materials have been investigated. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, such positive electrode active materials have problems such as the structure collapsing or cracking as charging and discharging are repeated, which reduces the long-term life of the lithium secondary battery and increases the resistance, making it impossible to show satisfactory capacity characteristics. Therefore, there is a need to develop a new positive electrode active material that can achieve high capacity and high energy density while ensuring long-term life characteristics. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a positive electrode active material for a lithium secondary battery that realizes high capacity while improving initial charge / discharge efficiency, life characteristics and safety, a method for producing the same, and a lithium secondary battery including the same. [Means for solving the problem]
[0005] In one embodiment, the present invention provides a positive electrode active material for a lithium secondary battery, the positive electrode active material comprising: a first positive electrode active material including a lithium-nickel-based composite oxide, the first positive electrode active material including secondary particles formed by agglomeration of a plurality of primary particles, and a cobalt coating portion located on a surface of the secondary particles; and a second positive electrode active material including a lithium-nickel-based composite oxide, the second positive electrode active material including a single particle and a cobalt coating portion located on a surface of the single particle, the single particle of the second positive electrode active material having a high-concentration coating region with a cobalt content of 30 at% or more relative to the total amount of nickel and cobalt and a low-concentration coating region with a cobalt content of 25 at% or less on a surface thereof, the difference between the cobalt content relative to the total amount of nickel and cobalt in the high-concentration coating region and the cobalt content relative to the total amount of nickel and cobalt in the low-concentration coating region being 20 at% to 50 at%.
[0006] In another embodiment, there is provided a method for producing a positive electrode active material for a lithium secondary battery, the method including: mixing a first nickel-based hydroxide and a lithium raw material and performing a first heat treatment to prepare a first nickel-based oxide in the form of secondary particles in which a plurality of primary particles are aggregated; mixing a second nickel-based hydroxide and a lithium raw material and performing a second heat treatment to prepare a second nickel-based oxide in the form of single particles; and mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material and performing a third heat treatment to obtain the positive electrode active material for a lithium secondary battery.
[0007] In yet another embodiment, a lithium secondary battery is provided that includes a positive electrode containing the positive electrode active material, a negative electrode, and an electrolyte. Effect of the Invention
[0008] A positive electrode active material for a lithium secondary battery prepared according to an embodiment and a lithium secondary battery including the same can achieve high capacity and high energy density, and can exhibit excellent charge / discharge efficiency, life characteristics, and safety. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic diagram illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) image of a second positive electrode active material of Example 1. [Diagram 3] 1 is a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) image of a second positive electrode active material of Example 1. [Figure 4] 1 is a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) image of a second positive electrode active material of Example 1. [Diagram 5] 1 is a SEM-EDS analysis image of a second positive electrode active material of Comparative Example 1. [Figure 6] 1 is a SEM-EDS analysis image of a second positive electrode active material of Comparative Example 1. [Figure 7] 1 is a SEM-EDS analysis image of a second positive electrode active material of Comparative Example 1. [Figure 8] 1 is a SEM-EDS analysis image of a fracture surface of a second positive electrode active material of Example 1. [Figure 9] 1 is a SEM-EDS analysis image of a fracture surface of a second positive electrode active material of Example 1. [Figure 10] 1 is a SEM-EDS analysis image of a fracture surface of a second positive electrode active material of Example 1. [Figure 11] 1 is a SEM-EDS analysis image of a fracture surface of a second positive electrode active material of Comparative Example 1. [Figure 12] 1 is a SEM-EDS analysis image of a fracture surface of a second positive electrode active material of Comparative Example 1. [Figure 13] 1 is a SEM-EDS analysis image of a fracture surface of a second positive electrode active material of Comparative Example 1. [Figure 14] 1 is a SEM-EDS image of a second positive electrode active material of Example 1. [Figure 15] 1 is a SEM-EDS image of a second positive electrode active material of Example 1. [Figure 16] 1 is a SEM-EDS image of a second positive electrode active material of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is not limited to the embodiments described herein, but may be embodied in many different forms, and should not be construed as limited to the embodiments described herein.
[0011] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0012] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.
[0013] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, and do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.
[0014] In the drawings, the thickness of the various layers and regions is exaggerated for clarity, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, plate, etc. is said to be "on" or "on" another part, this includes not only the case where it is "directly on" another part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.
[0015] In addition, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.
[0016] The average particle size can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer or by using a transmission electron microscope or a scanning electron microscope. Alternatively, the average particle size can be calculated by measuring the number of particles in each particle size range using a dynamic light scattering method and performing data analysis. Unless otherwise defined, the average particle size can refer to the diameter of particles whose cumulative volume is 50% by volume (D50) in the particle size distribution.
[0017] As used herein, "or" is not to be construed in its exclusive sense; for example, "A or B" is to be construed as including A, B, A+B, etc.
[0018] positive electrode active material In one embodiment, a positive electrode active material for a lithium secondary battery is provided, the positive electrode active material including a first positive electrode active material including a lithium nickel-based composite oxide and including a secondary particle formed by agglomerating a plurality of primary particles and a cobalt coating portion located on the surface of the secondary particle; and a second positive electrode active material including a lithium nickel-based composite oxide and including a single particle and a cobalt coating portion located on the surface of the single particle. Here, the surface of the single particle of the second positive electrode active material is characterized in that a high-concentration coating region having a cobalt content of 30 at% or more relative to the total amount of nickel and cobalt and a low-concentration coating region having a cobalt content of 25 at% or less exist, and the difference between the cobalt content of the high-concentration coating region relative to the total amount of nickel and cobalt and the cobalt content of the low-concentration coating region is 20 at% to 50 at%. This positive electrode active material realizes high capacity and high energy density, while the efficiency of the second positive electrode active material in the form of a single particle is increased, and the initial charge / discharge efficiency and life characteristics are improved overall, improving the safety of the battery.
[0019] First positive electrode active material The first positive active material has a polycrystal form and includes secondary particles formed by agglomerating at least two or more primary particles.
[0020] According to an embodiment, the first positive electrode active material includes a cobalt coating portion located on a surface of a secondary particle. The cobalt coating portion may be disposed on the entire surface of the secondary particle or at least a portion of the surface of the secondary particle. The first positive electrode active material is coated with cobalt, which effectively prevents the structure from collapsing due to repeated charging and discharging, thereby improving the room temperature and high temperature life characteristics.
[0021] The cobalt coating portion includes a cobalt-containing compound. The cobalt-containing compound may be, for example, cobalt oxide, cobalt hydroxide, cobalt carbonate, a composite thereof, or a mixture thereof, and may further include lithium and / or nickel. For example, the cobalt-containing compound may be lithium cobalt oxide.
[0022] In the first positive electrode active material, the content of the cobalt coating portion may be 0.01 mol% to 7 mol% relative to 100 mol% of all metals excluding lithium in the entire first positive electrode active material, for example, 0.01 mol% to 6 mol%, 0.1 mol% to 5 mol%, or 0.5 mol% to 3 mol%, or may be 0.01 atomic% to 7 atomic%, 0.1 atomic% to 5 atomic%, or 0.5 atomic% to 3 atomic% relative to 100 atomic% of all metals excluding lithium. In this case, a lithium secondary battery including the first positive electrode active material may achieve excellent room temperature and high temperature life characteristics.
[0023] In the first positive electrode active material, the thickness of the cobalt coating portion varies depending on the baking temperature during coating, and depending on the baking temperature, cobalt may penetrate into the active material to be coated and / or doped. Thus, the thickness of the cobalt coating portion may be, for example, 1 nm to 2 μm, 1 nm to 1.5 μm, 1 nm to 1 μm, 1 nm to 900 nm, 1 nm to 700 nm, 1 nm to 500 nm, 1 nm to 300 nm, 5 nm to 100 nm, or 5 nm to 50 nm. In this case, a lithium secondary battery including the first positive electrode active material may exhibit excellent room temperature and high temperature life characteristics. Here, the thickness of the cobalt coating portion may be measured through an electron microscope photograph of the active material.
[0024] The average particle size (D50) of the first positive electrode active material, i.e., the average particle size of the secondary particles, may be 7 μm to 25 μm. For example, it may be 9 μm to 25 μm, 10 μm to 25 μm, 15 μm to 25 μm, or 10 μm to 20 μm. The average particle size of the secondary particles of the first positive electrode active material may be the same as or larger than the average particle size of the second positive electrode active material of single particles described below. The positive electrode active material according to an embodiment may be in a form in which the first positive electrode active material, which is polycrystalline but large particles, and the second positive electrode active material, which is single particle but small particles, are mixed, thereby improving the mixture density and realizing high capacity and high energy density. Here, the average particle size of the first positive electrode active material may be obtained by measuring the particle size of about 30 active materials in the form of secondary particles in an electron microscope photograph of the positive electrode active material, and taking the diameter (D50) of the particle at 50% of the cumulative volume in the particle size distribution as the average particle size.
[0025] The first positive electrode active material is a nickel-based positive electrode active material and includes a lithium nickel-based composite oxide (or a first nickel-based oxide). In the lithium nickel-based composite oxide, the nickel content may be 30 mol% or more based on the total amount of elements excluding lithium and oxygen, for example, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and may be 99.9 mol% or less, or 99 mol% or less. For example, in the lithium nickel-based composite oxide, the nickel content may be higher than the contents of other elements such as cobalt, manganese, and aluminum. When the nickel content satisfies the above range, the positive electrode active material can exhibit excellent battery performance while achieving a high capacity.
[0026] Specifically, the first positive electrode active material may include a lithium nickel-based composite oxide represented by the following Chemical Formula 1.
[0027] [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O2 In the above formula 1, 0.9≦a1≦1.8, 0.3≦x1≦1, 0≦y1≦0.7, M 1 and M. 2 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0028] In the above Chemical Formula 1, 0.4≦x1≦1 and 0≦y1≦0.6 may be satisfied, or 0.5≦x1≦1 and 0≦y1≦0.5 may be satisfied, or 0.6≦x1≦1 and 0≦y1≦0.4 may be satisfied, or 0.7≦x1≦1 and 0≦y1≦0.3 may be satisfied, or 0.8≦x1≦1 and 0≦y1≦0.2 may be satisfied, or 0.9≦x1≦1 and 0≦y1≦0.1 may be satisfied.
[0029] The first positive electrode active material may include, for example, a lithium nickel-based composite oxide represented by the following Chemical Formula 2.
[0030] [Chemical formula 2] Li a2 Ni x2 Co y2 M 3 1-x2-y2 O2 In the above chemical formula 2, 0.9≦a2≦1.8, 0.3≦x2<1, 0 <y2≦0.7であり、M 3 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0031] In the above Chemical Formula 2, 0.3≦x2≦0.99 and 0.01≦y2≦0.7 may be satisfied, or 0.4≦x2≦0.99 and 0.01≦y2≦0.6 may be satisfied, or 0.5≦x2≦0.99 and 0.01≦y2≦0.5 may be satisfied, or 0.6≦x2≦0.99 and 0.01≦y2≦0.4 may be satisfied, or 0.7≦x2≦0.99 and 0.01≦y2≦0.3 may be satisfied, or 0.8≦x2≦0.99 and 0.01≦y2≦0.2 may be satisfied, or 0.9≦x2≦0.99 and 0.01≦y2≦0.1 may be satisfied.
[0032] The first positive electrode active material may include, for example, a compound represented by Formula 3 below. [Chemical formula 3] Li a3 Ni x3 Co y3 M 4 z3 M 5 1-x3-y3-z3 O2 In the above chemical formula 3, 0.9≦a3≦1.8, 0.3≦x3≦0.98, 0.01≦y3≦0.69, and 0.01≦z3≦0.69; M 4 is one or more elements selected from the group consisting of Al and Mn, 5is one or more elements selected from the group consisting of B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0033] In the formula 3, 0.4≦x3≦0.98, 0.01≦y3≦0.59, and 0.01≦z3≦0.59 may be satisfied, 0.5≦x3≦0.98, 0.01≦y3≦0.49, and 0.01≦z3≦0.49 may be satisfied, or 0.6≦x3≦0.98, 0.01≦y3≦0.39, and 0.01≦z3≦0.39 may be satisfied. or 0.7≦x3≦0.98, 0.01≦y3≦0.29, and 0.01≦z3≦0.29, or 0.8≦x3≦0.98, 0.01≦y3≦0.19, and 0.01≦z3≦0.19, or 0.9≦x3≦0.98, 0.01≦y3≦0.09, and 0.01≦z3≦0.09.
[0034] Second positive electrode active material The second positive electrode active material is in the form of a single particle, which means that the particle does not have a grain boundary within the particle and exists alone, and may mean a single particle, a monolith structure, a single body structure, or a non-aggregated particle in which the particles are not aggregated with each other in the morphological phase, and may be a single crystal, for example. The positive electrode active material according to an embodiment includes the second positive electrode active material in the form of such a single particle, and thereby can exhibit improved life characteristics while realizing high capacity and high energy density.
[0035] The shape of the second positive electrode active material is not particularly limited, and may have various shapes such as polyhedron, sphere, ellipse, plate, rod, amorphous, etc. According to an embodiment, the second positive electrode active material of a single particle may have a polyhedron structure having two or more faces.
[0036] According to an embodiment, the second positive electrode active material includes a cobalt-coated portion located on a surface of a single particle of the second positive electrode active material. By being coated with cobalt, the second positive electrode active material can effectively prevent the structure from collapsing due to repeated charging and discharging, thereby improving the room temperature and high temperature life characteristics.
[0037] The cobalt coating portion includes a cobalt-containing compound. The cobalt-containing compound may be, for example, cobalt oxide, cobalt hydroxide, cobalt carbonate, a composite thereof, or a mixture thereof, and may further include lithium and / or nickel. For example, the cobalt-containing compound may be lithium cobalt oxide.
[0038] In one embodiment, the cobalt-containing compound is evenly distributed over the entire surface of the single particle of the second positive electrode active material, but is coated on a portion of the surface of the single particle in a high content, thereby improving battery performance and increasing safety. Specifically, the surface of the single particle has a high-concentration coating region in which the cobalt content relative to the total amount of nickel and cobalt is 30 at% or more and a low-concentration coating region in which the cobalt content relative to the total amount of nickel and cobalt is 25 at% or less, and the difference between the cobalt content relative to the total amount of nickel and cobalt in the high-concentration coating region and the cobalt content relative to the total amount of nickel and cobalt in the low-concentration coating region is 20 at% to 50 at%. When such a second positive electrode active material is used, the initial charge / discharge efficiency and life characteristics of the battery can be improved compared to when a cobalt-containing compound is evenly coated over the entire surface of the single particle.
[0039] The high-concentration coating region is defined as a region in which the cobalt content relative to the total amount of nickel and cobalt on the surface of a single particle is 30 at% or more, for example, the cobalt content may be 30 at% to 70 at%, 30 at% to 60 at%, or 40 at% to 70 at%. Such a high-concentration coating region may occupy 30% to 80% of the entire surface area of the single particle, for example, 30% to 70%, or 40% to 80%.
[0040] A low-concentration coating region having a cobalt content of 25 at% or less based on the total amount of nickel and cobalt is also present on the surface of the single particle of the second positive electrode active material, and the low-concentration coating region may occupy 10% or more of the total area of the single particle surface.
[0041] The low-concentration coating region is defined as a region in which the cobalt content relative to the total amount of nickel and cobalt on the surface of a single particle is 25 at% or less, and for example, the cobalt content may be 0 at% to 25 at%, 5 at% to 25 at%, or 10 at% to 20 at%. Such a low-concentration coating region may occupy 10% or more of the entire surface area of the single particle, for example, 10% to 70%, 10% to 50%, 10% to 30%, or 10% to 20%. When the high-concentration coating region and the low-concentration coating region are present on the surface of the single particle in the above area ranges, the initial charge-discharge efficiency and life characteristics can be improved compared to when the cobalt-containing compound is evenly coated or when the cobalt-containing compound is not coated.
[0042] The difference between the content of cobalt relative to the total amount of nickel and cobalt in the high-concentration coating region and the content of cobalt relative to the total amount of nickel and cobalt in the low-concentration coating region may be 20 at% to 50 at%, for example, 20 at% to 45 at%, or 25 at% to 40 at%. When the difference in cobalt content between the high-concentration coating region and the low-concentration coating region is as described above, the efficiency of the single-particle second positive electrode active material can be increased.
[0043] According to an embodiment, the second positive electrode active material is different from an active material in which the cobalt content is high, 30 at% or more, relative to the total amount of nickel and cobalt in the lithium nickel-based composite oxide itself inside the active material, and the cobalt content is also high on the surface, and corresponds to an active material in which a high-concentration coating region having a cobalt content of 30 at% or more is formed on a part of the surface by coating with a cobalt-containing compound. For example, the cobalt content relative to the total amount of nickel and cobalt inside a single particle of the second positive electrode active material may be 0 at% to 10 at%, for example, 0.1 at% to 8 at%, or 0.1 at% to 6 at%, or may be 0 mol% to 10 mol%, 0.1 mol% to 8 mol%, or 0.1 mol% to 6 mol%. The difference between the content of cobalt relative to the total amount of nickel and cobalt in the high concentration coating region on the surface of the second positive electrode active material and the content of cobalt relative to the total amount of nickel and cobalt inside the second positive electrode active material may be about 20 at% or more, 30 at% or more, or 40 at% or more. Such a second positive electrode active material can achieve high capacity and long life characteristics.
[0044] Meanwhile, the average cobalt content relative to the total amount of nickel and cobalt on the surface of a single particle of the second positive electrode active material may be 20 at% to 60 at%, for example, 20 at% to 50 at%, or 25 at% to 45 at%. The average value may refer to an arithmetic average of concentrations measured at about 5 to 10 portions of the surface of a single particle, regardless of whether the concentration is high or low.
[0045] In the second positive electrode active material, the difference between the average cobalt content relative to the total amount of nickel and cobalt on the surface of the single particle and the cobalt content relative to the total amount of nickel and cobalt inside the single particle may be 10 at% to 60 at%, for example, 20 at% to 50 at%, or 25 at% to 45 at%. In this case, the second positive electrode active material can exhibit high efficiency and life characteristics while achieving high capacity.
[0046] In one embodiment, the cobalt content relative to the total amount of nickel and cobalt on the surface of the positive active material may be measured by performing scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) on the surface of the positive active material to obtain the nickel and cobalt contents through quantitative analysis, and then calculating the ratio of the cobalt content relative to the total amount. The cobalt content relative to the total amount of nickel and cobalt inside the positive active material may be measured through SEM-EDS analysis of a fracture surface of the positive active material. As a method for measuring the cobalt content, inductively coupled plasma-mass spectrometry (ICP-MS) or inductively coupled plasma optical emission spectroscopy (ICP-OES) may be used in addition to SEM-EDS.
[0047] The second positive electrode active material includes a lithium nickel-based composite oxide (or a second nickel-based oxide) as a nickel-based active material. In the lithium nickel-based composite oxide, the nickel content may be 60 mol% or more based on the total amount of elements excluding lithium and oxygen, for example, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and 99.9 mol% or less, or 99 mol% or less. For example, in the lithium nickel-based composite oxide, the nickel content may be higher than the respective contents of other metals such as cobalt, manganese, and aluminum. When the nickel content satisfies the above range, the positive electrode active material can exhibit excellent battery performance while achieving a high capacity.
[0048] The second positive electrode active material can include, for example, a lithium nickel-based composite oxide represented by the following chemical formula 11. [Chemical formula 11] Li a11 Ni x11 Co y11 M 11 1-x11-y11 O2 In the above formula 11, 0.9≦a11≦1.8, 0.6≦x11≦1, and 0≦y11≦0.1; M 11 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0049] In Chemical Formula 11, x11, which indicates the content of Ni, may be, for example, 0.7≦x11≦1, 0.8≦x11≦1, or 0.9≦x11≦1. When the content of nickel is 90 mol% or more, a very high capacity can be achieved, and the cobalt coating portion according to an embodiment can suppress problems such as collapse of the structure, cracks, or side reactions during the life of the battery.
[0050] The average particle size of the second positive electrode active material, i.e., the average particle size of the single particle, may be 0.05 μm to 7 μm, for example, 0.05 μm to 7 μm, 0.1 μm to 6 μm, 0.5 μm to 5 μm, or 0.5 μm to 7 μm. The particle size of the second positive electrode active material may be the same as or smaller than that of the first positive electrode active material, thereby further increasing the density of the positive electrode active material. Here, the average particle size of the second positive electrode active material may be determined by measuring the particle size of about 30 single particle active materials selected randomly from an electron microscope photograph of the positive electrode active material, and taking the diameter (D50) of the particle with a cumulative volume of 50% by volume in the particle size distribution as the average particle size.
[0051] The BET specific surface area of the entire positive electrode active material including the first positive electrode active material and the second positive electrode active material is 0.2 m 2 / g~0.6m 2 / g, for example 0.3m 2 / g~approx.0.5m 2 / g, 0.3m 2 / g~approx.0.4m 2 / g. In this case, the positive electrode active material can realize excellent charge / discharge efficiency and life characteristics. The BET specific surface area may be measured by a nitrogen gas adsorption method using, for example, a specific surface area measuring device HM model-1208 manufactured by MOUNTECH. Specifically, about 0.3 g of a positive electrode active material sample is heated in a nitrogen atmosphere at 300°C in a pretreatment device for 1 hour, then pretreated for an additional 15 minutes at 300°C in a specific surface area measuring device, cooled to the temperature of liquid nitrogen, and saturated adsorbed with a gas of 30% nitrogen and 70% He. Thereafter, the amount of gas desorbed by heating to room temperature is measured, and the specific surface area can be calculated from the obtained results by a conventional BET method.
[0052] In the positive electrode active material according to an embodiment, the first positive electrode active material may be included in a range of 50 wt% to 90 wt% and the second positive electrode active material may be included in a range of 10 wt% to 50 wt% based on the total amount of the first positive electrode active material and the second positive electrode active material. The first positive electrode active material may be included in a range of, for example, 60 wt% to 90 wt% or 70 wt% to 90 wt%, and the second positive electrode active material may be included in a range of, for example, 10 wt% to 40 wt% or 10 wt% to 30 wt%. When the content ratio of the first positive electrode active material to the second positive electrode active material is as described above, the positive electrode active material including the first positive electrode active material and the second positive electrode active material may achieve a high capacity and exhibit a high energy density due to an improved mixture density.
[0053] Method for producing positive electrode active material In one embodiment, a method for producing a positive electrode active material for a lithium secondary battery is provided, the method including: mixing a first nickel-based hydroxide and a lithium raw material and performing a first heat treatment to prepare a first nickel-based oxide in the form of secondary particles in which a plurality of primary particles are aggregated; mixing a second nickel-based hydroxide and a lithium raw material and performing a second heat treatment to prepare a second nickel-based oxide in the form of single particles; mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material and performing a third heat treatment to obtain a final positive electrode active material including the first positive electrode active material and the second positive electrode active material.
[0054] The first positive electrode active material is a material in which a cobalt-containing compound is coated on the surface of a first nickel-based oxide, and the second positive electrode active material is a material in which a cobalt-containing compound is coated on the surface of a second nickel-based oxide.
[0055] In one embodiment, the first and second positive active materials are not individually cobalt-coated, but the first and second nickel-based oxides are mixed and cobalt-coated at the same time. In this manner, instead of the cobalt-containing compound being evenly coated on the surface of the single particles of the second positive active material, the cobalt-containing compound is coated in a high content only on one side, thereby increasing the efficiency of the single particles and improving the initial charge / discharge efficiency and life characteristics of the lithium secondary battery including the same.
[0056] The first nickel-based hydroxide and the second nickel-based hydroxide are precursors of a positive electrode active material, and each may independently be a nickel hydroxide or a nickel-based composite hydroxide containing elements other than nickel, a nickel-metal composite hydroxide containing metals other than nickel, or a nickel-transition metal composite hydroxide containing transition metals other than nickel.
[0057] For example, the first nickel hydroxide may be represented by the following chemical formula 21. [Chemical formula 21] Ni x21 M 21 y21 M 22 1-x21-y21 (OH)2 In the above formula 21, 0.3≦x21≦1, 0≦y21≦0.7, M 21 and M. 22 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0058] The second nickel hydroxide may be represented by the following chemical formula 31. [Chemical formula 31] Ni x31 Co y31 M 31 1-x31-y31 (OH)2 In the above formula 31, 0.6≦x31≦1 and 0≦y31≦0.1, M 31 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0059] The particle size of the first nickel-based hydroxide and the second nickel-based hydroxide may be independently 1 μm to 30 μm, for example, 1 μm to 25 μm, 1 μm to 20 μm, or 5 μm to 20 μm. The particle size of the nickel-based hydroxide is measured by a particle size analyzer using laser diffraction, and may mean the diameter of particles with a cumulative volume of 50% by volume in the particle size distribution (D50).
[0060] The lithium source is a lithium source for the positive electrode active material and may be, for example, Li2CO3, LiOH, hydrates thereof, or combinations thereof.
[0061] When the first nickel-based hydroxide and the lithium raw material are mixed, the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the first nickel-based hydroxide may be, for example, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1.0 or more, and may be 1.8 or less, 1.5 or less, 1.2 or less, 1.1 or less, or 1.05 or less.
[0062] The first heat treatment can be performed in an oxidizing gas atmosphere, for example, in an oxygen atmosphere or an air atmosphere. The first heat treatment can be performed at, for example, 600°C to 900°C or 600°C to 800°C, for example, for 5 to 20 hours or 5 to 15 hours. The first nickel-based oxide obtained through the first heat treatment can also be called a first lithium nickel-based oxide or a first nickel-based composite oxide.
[0063] When the second nickel-based hydroxide and the lithium raw material are mixed, the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the second nickel-based hydroxide may be, for example, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1.0 or more, and may be 1.8 or less, 1.5 or less, 1.2 or less, 1.1 or less, or 1.05 or less.
[0064] The second heat treatment can also be performed in an oxidizing gas atmosphere, for example, in an oxygen atmosphere or an air atmosphere. The second heat treatment can be performed at, for example, 800°C to 1100°C or 900°C to 1000°C, for example, for 5 to 20 hours or 5 to 15 hours. The second nickel-based oxide obtained through the second heat treatment can also be expressed as a second lithium nickel-based oxide or a second nickel-based composite oxide.
[0065] The second nickel-based oxide has a single particle form, and the single particle form can be obtained by adjusting conditions such as the temperature and time of the second heat treatment, and the single particle form can also be obtained through various conditions when synthesizing the second nickel-based hydroxide by a co-precipitation method.
[0066] The method for producing a positive electrode active material for a lithium secondary battery may further include mixing the second nickel-based hydroxide and the lithium raw material, subjecting the mixture to a second heat treatment, and then pulverizing the resulting mixture, thereby obtaining a single particle of the second nickel-based oxide. The pulverization may be performed using various pulverizing devices such as a jet mill. Here, the pulverization of the resulting mixture is a process for obtaining a single particle of active material, and is different from the crushing of a general active material.
[0067] In the process of mixing the first nickel-based oxide and the second nickel-based oxide, the weight ratio of the first nickel-based oxide to the second nickel-based oxide may be 9:1 to 5:5, for example, 9:1 to 6:4, or 8:2 to 7:3. When the mixing ratio of the first nickel-based oxide to the second nickel-based oxide satisfies the above range, the produced positive electrode active material can exhibit high capacity and high energy density, and can exhibit high plate density.
[0068] Next, the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material are mixed and subjected to a third heat treatment to perform cobalt coating. The cobalt raw material may be, for example, cobalt hydroxide, cobalt carbonate, cobalt sulfate, cobalt oxide, cobalt nitrate, etc. The cobalt raw material may be mixed so that the amount of cobalt contained in the cobalt raw material is 0.01 to 7 molar parts, 0.01 to 5 molar parts, or 0.1 to 4 molar parts, etc., when the content of metals other than lithium in the entire positive electrode active material is 100 molar parts.
[0069] Cobalt coating can be performed in a dry or wet manner. For example, dry coating can be performed by mixing the first nickel-based oxide, the second nickel-based oxide, and the cobalt raw material without a solvent, and then performing the third heat treatment. Alternatively, the first nickel-based oxide and the second nickel-based oxide can be added to a solvent such as distilled water, mixed and washed, and the cobalt raw material can be dropped to perform wet coating and the third heat treatment.
[0070] In one embodiment, when the first nickel-based oxide, the second nickel-based oxide, and the cobalt compound are mixed, a lithium raw material may be mixed together. The lithium raw material may be, for example, Li2CO3, LiOH, a hydrate thereof, or a combination thereof. The lithium raw material may be mixed at 1 to 4 molar parts with respect to 1 molar part of the cobalt compound to be added together, for example, 1.5 to 3 molar parts. That is, the lithium raw material may be added 1 to 4 times or 1.5 to 3 times the amount of the cobalt compound. Alternatively, the lithium raw material may be mixed at 0.01 to 10 molar parts, 0.1 to 8 molar parts, or 1 to 6 molar parts with respect to 100 molar parts of the metal content excluding lithium in the entire positive electrode active material. When the lithium raw material is added together in the cobalt coating step, a stable cobalt coating part may be formed on the surface of the positive electrode active material, and according to one embodiment, a cobalt coating part may be formed in a form in which a high-concentration coating region occupies 30% to 80% of the surface of the single particle. This makes it possible to improve the initial charge / discharge efficiency of the lithium secondary battery and to enhance its life characteristics.
[0071] In one embodiment, when the cobalt coating is performed by a wet method, a pH adjuster such as sodium hydroxide may be added when the first nickel-based oxide, the second nickel-based oxide, and the cobalt compound are mixed. The pH adjuster may be added in an amount of 0.5 to 5 molar parts per 1 molar part of the cobalt compound. In this manner, the cobalt coating part according to one embodiment can be effectively formed by using the pH adjuster.
[0072] The third heat treatment can be performed in an oxidizing gas atmosphere such as oxygen or air, for example, at 650° C. to 900° C. or 650° C. to 800° C. The third heat treatment time varies depending on the heat treatment temperature, but is performed for example, 5 to 30 hours or 10 to 24 hours.
[0073] Then, the heat treatment is terminated and the mixture is cooled to room temperature to manufacture the positive electrode active material for a lithium secondary battery according to the embodiment. The manufactured positive electrode active material is a mixture of the first positive electrode active material including secondary particles formed by agglomeration of primary particles and the second positive electrode active material in the form of a single particle, and the surface of the single particle of the second positive electrode active material has a high-concentration coating region in which the cobalt content relative to the total amount of nickel and cobalt is 30 at% or more and a low-concentration coating region in which the cobalt content relative to the total amount of nickel and cobalt is 25 at% or less, and the difference between the cobalt content relative to the total amount of nickel and cobalt in the high-concentration coating region and the cobalt content relative to the total amount of nickel and cobalt in the low-concentration coating region is 20 at% to 50 at%.
[0074] positive electrode A positive electrode for a lithium secondary battery may include a current collector and a positive electrode active material layer located on the current collector. The positive electrode active material layer includes a positive electrode active material, and may further include a binder and / or a conductive material.
[0075] The binder serves to adhere the positive electrode active material particles to each other well and to the current collector well. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, and the like.
[0076] The content of the binder in the positive electrode active material layer may be about 1% by weight to 5% by weight based on the total weight of the positive electrode active material layer.
[0077] The conductive material is used to impart conductivity to the electrodes, and any material that does not cause a chemical change in the constructed battery and is electronically conductive can be used. Examples of conductive materials that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers containing copper, nickel, aluminum, silver, and the like; conductive polymers such as polyphenylene derivatives; and conductive materials containing mixtures of these.
[0078] The content of the conductive material in the positive electrode active material layer may be 1 wt % to 5 wt % based on the total weight of the positive electrode active material layer.
[0079] The positive electrode current collector may be made of aluminum foil, but is not limited thereto.
[0080] negative electrode The negative electrode for a lithium secondary battery includes a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material layer includes a negative electrode active material, and may further include a binder and / or a conductive material.
[0081] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of being doped and dedoped with lithium, or a transition metal oxide.
[0082] The material capable of reversibly intercalating / deintercalating lithium ions may be a carbon-based negative electrode active material, and may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, and calcined coke.
[0083] As an alloy of lithium metal, an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.
[0084] As a substance capable of doping and undoping lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material can be used. As the Si-based negative electrode active material, silicon, a silicon-carbon composite, SiO x (0 < x < 2), a Si-Q alloy (wherein Q is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, and is not Si), and as the Sn-based negative electrode active material, Sn, SnO2, a Sn-R alloy (wherein R is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, and is not Sn), etc. can be mentioned, and at least one of these can also be mixed with SiO2 and used. As the elements Q and R, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof can be selected and used.
[0085] The silicon-carbon composite may be, for example, a silicon-carbon composite including a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. As the amorphous carbon precursor, coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or polymer resin such as phenol resin, furan resin, polyimide resin, etc. may be used. In this case, the content of silicon may be 10% by weight to 50% by weight based on the total weight of the silicon-carbon composite. The content of crystalline carbon may be 10% by weight to 70% by weight based on the total weight of the silicon-carbon composite, and the content of amorphous carbon may be 20% by weight to 40% by weight based on the total weight of the silicon-carbon composite. The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle size (D50) of the silicon particles may be 10 nm to 20 μm. The average particle size (D50) of the silicon particles may be preferably 10 nm to 200 nm. The silicon particles are present in an oxidized form, and the atomic ratio of Si:O in the silicon particles, which indicates the degree of oxidation, may be 99:1 to 33:67. x In this case, SiO x In the above, x may range from more than 0 to less than 2. Unless otherwise defined herein, the average particle size (D50) refers to the diameter of particles whose cumulative volume is 50% by volume in the particle size distribution.
[0086] The Si-based or Sn-based negative electrode active material can be mixed with a carbon-based negative electrode active material. When the Si-based or Sn-based negative electrode active material is mixed with a carbon-based negative electrode active material, the mixing ratio by weight can be 1:99 to 90:10.
[0087] The content of the negative active material in the negative active material layer may be 95 wt % to 99 wt % based on the total weight of the negative active material layer.
[0088] In one embodiment, the negative electrode active material layer further includes a binder, and may optionally further include a conductive material. The content of the binder in the negative electrode active material layer may be 1 wt% to 5 wt% based on the total weight of the negative electrode active material layer. In addition, when the conductive material is further included, the negative electrode active material layer may include 90 wt% to 98 wt% of the negative electrode active material, 1 wt% to 5 wt% of the binder, and 1 wt% to 5 wt% of the conductive material.
[0089] The binder serves to adhere the negative active material particles to each other and to the current collector, and may be a water-insoluble binder, a water-soluble binder, or a combination thereof.
[0090] The water insoluble binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, ethylene propylene copolymers, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or combinations thereof.
[0091] The water-soluble binder may be a rubber-based binder or a polymeric resin binder. The rubber-based binder may be selected from styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. The polymeric resin binder may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0092] When a water-soluble binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be used in combination. As the alkali metal, Na, K, or Li may be used. The content of such a thickener may be 0.1 to 3 parts by weight based on 100 parts by weight of the negative electrode active material.
[0093] The conductive material is used to impart conductivity to the electrodes, and any material that does not cause a chemical change in the constructed battery and is electronically conductive can be used. Examples of conductive materials that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers, including copper, nickel, aluminum, silver, and the like; conductive polymers such as polyphenylene derivatives; and mixtures of these.
[0094] The negative electrode current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0095] Lithium secondary battery Another embodiment provides a lithium secondary battery including a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and an electrolyte.
[0096] 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. Referring to FIG 1, a lithium secondary battery 100 according to an embodiment includes a battery cell including a positive electrode 114, a negative electrode 112 facing the positive electrode 114, a separator 113 disposed between the positive electrode 114 and the negative electrode 112, and a lithium secondary battery electrolyte impregnated in the positive electrode 114, the negative electrode 112, and the separator 113, a battery container 120 in which the battery cell is housed, and a sealing member 140 for sealing the battery container 120.
[0097] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0098] The non-aqueous organic solvent acts as a medium through which ions involved in the electrochemical reaction of the battery can move. As the non-aqueous organic solvent, carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvents can be used. As the carbonate-based solvent, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc. Examples of the ketone solvent include cyclohexanone, etc. In addition, examples of alcohol-based solvents that can be used include ethyl alcohol and isopropyl alcohol, and examples of aprotic solvents that can be used include nitriles such as R-CN (wherein R is a hydrocarbon group having a linear, branched, or cyclic structure with 2 to 20 carbon atoms and may contain a double bond, an aromatic ring, or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes.
[0099] The non-aqueous organic solvent may be used alone or in combination with one or more other solvents. When one or more other solvents are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which should be widely understood by those skilled in the art.
[0100] In addition, in the case of carbonate-based solvents, cyclic carbonates and chain carbonates can be mixed and used. In this case, the performance of the electrolyte is excellent when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9.
[0101] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent in addition to the carbonate solvent, and the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.
[0102] As the aromatic hydrocarbon solvent, an aromatic hydrocarbon compound represented by the following formula I can be used.
[0103] [ka]
[0104] In the above formula I, R 4 ~R 9 are the same or different and are selected from the group consisting of hydrogen, halogen, an alkyl group having 1 to 10 carbon atoms, a haloalkyl group having 1 to 10 carbon atoms, and combinations thereof.
[0105] Specific examples of aromatic hydrocarbon solvents include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, and fluoro. and n is selected from the group consisting of toluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, or combinations thereof.
[0106] The electrolyte may further contain vinylene carbonate or an ethylene carbonate-based compound of the following formula II as a life-promoting additive to improve the battery life.
[0107] [ka]
[0108] In the above formula II, R 10 and R 11 are the same or different and are selected from the group consisting of hydrogen, a halogen group, a cyano group, a nitro group, and a fluorinated alkyl group having 1 to 5 carbon atoms, 10 and R 11At least one of R is selected from the group consisting of a halogen group, a cyano group, a nitro group, and a fluorinated alkyl group having 1 to 5 carbon atoms, with the proviso that 10 and R 11 But it's not all hydrogen.
[0109] Representative examples of ethylene carbonate compounds include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, etc. When such life-improving additives are further used, the amount used can be appropriately adjusted.
[0110] A lithium salt is a substance that is dissolved in a non-aqueous organic solvent and acts as a source of lithium ions in a battery to enable basic lithium secondary battery operation and to facilitate the movement of lithium ions between the positive electrode and the negative electrode.
[0111] Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1and lithium difluoro(bisoxalato)borate (LiDFOB).
[0112] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. If the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance, and lithium ions can be effectively transferred.
[0113] The separator 113 separates the positive electrode 114 and the negative electrode 112 and provides a path for lithium ions to move, and can be any separator that is generally used in lithium ion batteries. That is, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability can be used. For example, the separator 113 can include glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene, or a combination thereof, and can be in the form of a nonwoven fabric or a woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium ion batteries, and coated separators containing ceramic components or polymer materials to ensure heat resistance or mechanical strength can also be used, and can be selectively used in a single-layer or multi-layer structure.
[0114] Lithium secondary batteries can be classified into lithium ion batteries, lithium ion polymer batteries, and lithium polymer batteries depending on the type of separator and electrolyte used, into cylindrical, square, coin, pouch, etc. types depending on the shape, and into bulk and thin film types depending on the size. The structure and manufacturing method of these batteries are widely known in this field, so a detailed description will be omitted.
[0115] The lithium secondary battery according to an embodiment has a high capacity and is excellent in storage stability, life characteristics, and high rate characteristics at high temperatures, and can be used in electric vehicles (EVs), hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs), and portable electronic devices.
[0116] Examples of the present invention and comparative examples are described below. The following examples are merely examples of the present invention, and the present invention is not limited to the following examples. EXAMPLES
[0117] Example 1 1. Preparation of primary nickel-based oxide in the form of secondary particles The metal raw materials, nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O), and manganese sulfate (MnSO4·H2O), were dissolved in distilled water as a solvent in a molar ratio of 95:4:1 to prepare a mixed solution, and 10% by weight of ammonia water (NH4OH) and 20% by weight of sodium hydroxide (NaOH) were prepared as a precipitating agent and a complex compound formation agent, respectively.
[0118] Ammonia water dilution is added to the continuous reactor, followed by continuous addition of the metal raw material mixed solution and sodium hydroxide to maintain the pH inside the reactor. The reaction is carried out slowly for about 80 hours, and when the reaction is stabilized, the overflowing product is collected and washed and dried to obtain the final precursor. As a result, the primary particles are aggregated to produce a first nickel hydroxide (Ni0.95 Co 0.04 Mn 0.01 (OH)2) is obtained, washed and dried.
[0119] The first nickel-based hydroxide and LiOH were mixed so that the mole ratio of lithium to the total metal amount of the first nickel-based hydroxide was 1.04, and the mixture was subjected to a first heat treatment at about 750°C for 15 hours in an oxygen atmosphere to obtain a first nickel-based oxide (LiNi 0.95 Co 0.04 Mn 0.01 The average particle size of the obtained first nickel-based oxide is about 15 μm, and the primary particles are aggregated to form secondary particles.
[0120] 2. Preparation of second nickel-based oxide in single particle form A mixed solution is prepared by dissolving nickel sulfate, cobalt sulfate, and manganese sulfate in distilled water as a solvent. A 10% by weight diluted ammonia water (NH4OH) solution is prepared to form a complex compound, and 20% by weight sodium hydroxide (NaOH) is prepared as a precipitant. The mixed metal raw material solution, ammonia water, and sodium hydroxide are then each placed into the reactor. The reaction is then carried out for approximately 20 hours while stirring. The slurry solution in the reactor is then filtered and washed with high-purity distilled water, and then dried for 24 hours to obtain a second nickel hydroxide (Ni 0.94 Co 0.05 Mn 0.01 The resulting second nickel hydroxide powder has an average particle size of about 4.0 μm and a specific surface area measured by the BET measurement method of about 15 m 2 / g.
[0121] The obtained second nickel-based hydroxide and LiOH are mixed to satisfy the molar ratio Li / (Ni+Co+Mn)=1.05, and then the mixture is put into a sintering furnace and subjected to a second heat treatment at 910°C for 8 hours in an oxygen atmosphere. The obtained material is then crushed for about 30 minutes to separate / disperse into a large number of second nickel-based oxides having a single particle form. The obtained second nickel-based oxide (LiNi 0.94 Co 0.05 Mn 0.01The average particle size of O2) is about 3.7 μm.
[0122] 3. Cobalt coating and final cathode active material fabrication The first nickel-based oxide and the second nickel-based oxide are mixed in a weight ratio of 7:3, and the weight ratio of this mixture to water is set to 1:1, followed by washing with water in a stirrer and drying at 150°C. 5 moles of lithium hydroxide and 2.5 moles of cobalt oxide are added to 100 moles of transition metals in the total nickel-based oxide, and the mixture is placed in a sintering furnace and subjected to a third heat treatment at about 710°C for 15 hours in an oxygen atmosphere. The sintering furnace is then cooled to room temperature to obtain a final positive electrode active material in which the first and second positive electrode active materials are mixed.
[0123] The final positive electrode active material is a mixture of the first positive electrode active material in the form of secondary particles and the second positive electrode active material in the form of single particles, each of which is coated with cobalt.
[0124] 4. Fabrication of the Positive Electrode 95% by weight of the final positive electrode active material, 3% by weight of polyvinylidene fluoride binder, and 2% by weight of carbon nanotube conductive material are mixed in N-methylpyrrolidone solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry is applied to an aluminum current collector, dried, and then rolled to prepare a positive electrode.
[0125] 5. Manufacturing of lithium secondary batteries A coin half cell is manufactured by using the prepared positive electrode and lithium metal counter electrode, placing a polyethylene polypropylene multilayer separator between them, and injecting an electrolyte solution of 1.0 M LiPF6 lithium salt added to a solvent of ethylene carbonate and diethyl carbonate mixed in a volume ratio of 50:50.
[0126] Comparative Example 1 A cathode active material and a battery are manufactured in the same manner as in Example 1, except that in “3. Preparation of cobalt coating and final cathode active material” of Example 1, the first nickel-based oxide and the second nickel-based oxide are not mixed and then cobalt-coated, but the first nickel-based oxide and the second nickel-based oxide are separately cobalt-coated and then mixed.
[0127] The cobalt coating process is as follows. 100 mole parts of transition metal, 5 mole parts of lithium hydroxide, and 2.5 mole parts of cobalt oxide are mixed with the first nickel-based oxide and put into a sintering furnace, and then a third heat treatment is performed at about 710°C in an oxygen atmosphere for 15 hours, and the sintering furnace is cooled to room temperature to obtain a first positive active material. 5 mole parts of lithium hydroxide and 2.5 mole parts of cobalt oxide are mixed with 100 mole parts of transition metal, and put into a sintering furnace, and then a third heat treatment is performed at about 850°C in an oxygen atmosphere for 15 hours, and the sintering furnace is cooled to room temperature to obtain a second positive active material. The first positive active material coated with cobalt and the second positive active material coated with cobalt are mixed in a weight ratio of 7:3 to prepare a final positive active material according to Comparative Example 1.
[0128] Evaluation example 1: Analysis of the surface and fracture surface of a single particle 2 to 4 are SEM-EDS analysis images of particles corresponding to the second positive active material in the final positive active material prepared in Example 1, in which the cobalt element is highlighted in light blue, and Figs. 8 to 10 are SEM-EDS analysis images of a fracture surface of the second positive active material in Example 1, in which the cobalt element is similarly highlighted in light blue.
[0129] 2 to 4 and 8 to 10, it can be seen that the cobalt element is not uniformly distributed on the surface of a single particle, but is concentrated and distributed at a high concentration on one surface.
[0130] 5 to 7 are SEM-EDS analysis images of the second positive electrode active material prepared according to Comparative Example 1, in which the cobalt element is highlighted in light blue, and Figs. 11 to 13 are SEM-EDS analysis images of the fracture surface of the second positive electrode active material prepared according to Comparative Example 1, in which the cobalt element is similarly highlighted in light blue.
[0131] 5 to 7 and 11 to 13, in the case of the second positive electrode active material according to Comparative Example 1, it can be seen that the cobalt element is evenly distributed on the surface of the single particle.
[0132] Evaluation example 2: Analysis of cobalt content on the surface of a single particle The surface of each of the second positive electrode active materials prepared in Example 1 and Comparative Example 1 was subjected to SEM-EDS analysis to measure the content of cobalt relative to the total amount of nickel and cobalt on the surface.
[0133] 14 and 15 are SEM-EDS analysis images of the second positive electrode active material of Example 1, and FIG. 16 is an SEM-EDS analysis image of the second positive electrode active material of Comparative Example 1. The cobalt content was measured at each numbered position, and the results are shown in Table 1 below.
[0134] [Table 1]
[0135] [Table 2]
[0136] As shown in Table 1, the second positive electrode active material of Example 1 is divided into a high-concentration coating region where the cobalt content is 30 at% or more and a low-concentration coating region where the cobalt content is 25 at% or less. The arithmetic mean value of the cobalt content in the high-concentration coating region is 52.9 at%, and the arithmetic mean value of the cobalt content in the low-concentration coating region is 18.3 at%, and the difference between the two values is calculated to be 34.6 at%. On the other hand, as shown in Table 2, in the second positive electrode active material of Comparative Example 1, the cobalt content is measured similarly over the entire single particle surface, and high-concentration and low-concentration regions are not distinguished, and the cobalt content over the entire single particle surface is confirmed to be 15.5 at% or less.
[0137] Evaluation example 3: Analysis of the difference in cobalt content between the surface and interior of a single particle The surface of each of the second positive electrode active materials prepared in Example 1 and Comparative Example 1 was subjected to SEM-EDS analysis to measure the cobalt content relative to the total amount of nickel and cobalt on the surface. In addition, the fracture surface of each of the second positive electrode active materials prepared in Example 1 and Comparative Example 1 was subjected to SEM-EDS analysis to measure the cobalt content relative to the total amount of nickel and cobalt inside a single particle. The difference between the cobalt content on the surface and the cobalt content inside was calculated and shown in Table 3 below. Here, the cobalt content on the surface and inside means an average value, and the values are calculated by arithmetically averaging the contents of 5 to 10 portions.
[0138] [Table 3]
[0139] Referring to Table 3, in the case of Example 1, the cobalt content on the surface of the second positive electrode active material is 35.61 at%, which is understood to be about 25 to 40 at% level, and in the case of Comparative Example 1, the cobalt content on the surface of the second positive electrode active material is 11.25 at%, which is understood to be about 10 to 20 at% level. As a result, it can be seen that there is a large difference in the content of cobalt coated on the surface of the second positive electrode active material depending on the difference in the coating method. In addition, the difference between the cobalt content on the surface of the single particle and the cobalt content inside the single particle is analyzed to be 29.61 at% in Example 1 and 5.25 at% in Comparative Example 1. It can be seen that the difference between the cobalt content on the surface and inside of the single particle is much larger in the case of Example 1 than in Comparative Example 1. It can be seen that the second positive electrode active material having such characteristics realizes high capacity and increases efficiency.
[0140] Evaluation example 4: Charge / discharge efficiency and life characteristics Each of the coin half cells of Example 1 and Comparative Example 2 was charged under constant current (0.2C) and constant voltage (4.25V, 0.05C cut-off) conditions to measure the charge capacity, and then the cells were rested for 10 minutes and discharged to 3.0V under constant current (0.2C) conditions to measure the discharge capacity. The ratio of the discharge capacity to the charge capacity is indicated as the efficiency. The results are shown in Table 4 below.
[0141] In addition, after the initial charge and discharge, the battery was charged and discharged 50 times at 45°C and 1C, and the discharge capacity after 50 times was measured. The ratio (%) of the 50th discharge capacity to the initial discharge capacity is shown in Table 4 as the capacity retention rate, i.e., the life characteristics.
[0142] [Table 4]
[0143] Referring to Table 4 above, it can be seen that Example 1 has an increased discharge capacity, improved charge / discharge efficiency, and improved high-temperature life characteristics compared to Comparative Example 1.
[0144] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the following claims also fall within the scope of the present invention. [Explanation of symbols]
[0145] 100: Lithium secondary battery 112: Negative electrode 113: Separation membrane 114: Positive electrode 120:Battery container 140: Encapsulating material
Claims
1. a first positive electrode active material including a lithium nickel-based composite oxide, the first positive electrode active material including secondary particles formed by agglomerating a plurality of primary particles and a cobalt coating portion located on a surface of the secondary particles; A positive electrode active material for a lithium secondary battery, comprising: a second positive electrode active material including a lithium nickel-based composite oxide, the second positive electrode active material including a single particle and a cobalt coating portion located on a surface of the single particle, a high-concentration coating region having a cobalt content of 30 at% or more and a low-concentration coating region having a cobalt content of 25 at% or less based on the total amount of nickel and cobalt on the surface of the single particle of the second positive electrode active material; The difference between the content of cobalt relative to the total amount of nickel and cobalt in the high concentration coating region and the content of cobalt relative to the total amount of nickel and cobalt in the low concentration coating region is 20 at% to 50 at%; The content of cobalt relative to the total amount of nickel and cobalt is measured by SEM-EDS analysis.
2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the content of cobalt in the single particle of the second positive electrode active material is 0 at % to 15 at % based on the total amount of nickel and cobalt.
3. the average content of cobalt relative to the total amount of nickel and cobalt on the surface of the single particle of the second positive electrode active material is 20 at% to 60 at%; 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the content of cobalt relative to the total amount of nickel and cobalt is measured by SEM-EDS analysis.
4. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a difference between an average value of a cobalt content relative to a total amount of nickel and cobalt on the surface of the single particle and a cobalt content relative to a total amount of nickel and cobalt inside the single particle is 10 at % to 60 at %.
5. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium nickel-based composite oxide of the second positive electrode active material is represented by the following chemical formula 11: [Chemical formula 11] Li a11 Ni x11 Co y11 M 11 1-x11-y11 O 2 In the above formula 11, 0.9≦a11≦1.8, 0.6≦x11≦1, and 0≦y11≦0.15; M 11 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
6. 6. The positive electrode active material for a lithium secondary battery according to claim 5, wherein in said chemical formula 11, 0.9≦x11≦1 and 0≦y11≦0.
1.
7. The average particle size of the first positive electrode active material is 7 μm to 25 μm, 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size of the second positive electrode active material is 1 μm to 7 μm.
8. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the first positive electrode active material is contained in an amount of 50% by weight to 90% by weight, and the second positive electrode active material is contained in an amount of 10% by weight to 50% by weight, based on the total amount of the first positive electrode active material and the second positive electrode active material.
9. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium nickel-based composite oxide of the first positive electrode active material is represented by the following chemical formula 1: [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2 In the above formula 1, 0.9≦a1≦1.8, 0.3≦x1≦1, 0≦y1≦0.7, M 1 and M. 2 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
10. preparing a first nickel-based oxide in the form of secondary particles in which a plurality of primary particles are aggregated by mixing a first nickel-based hydroxide and a lithium source and performing a first heat treatment on the mixture; Mixing the second nickel-based hydroxide and the lithium raw material and subjecting the mixture to a second heat treatment to prepare a second nickel-based oxide in the form of a single particle; mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material and subjecting the mixture to a third heat treatment; A method for producing a positive electrode active material for a lithium secondary battery, comprising obtaining the positive electrode active material for a lithium secondary battery according to any one of claims 1 to 9.
11. The first nickel hydroxide is represented by the following chemical formula 21: The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the second nickel-based hydroxide is represented by the following chemical formula 31: [Chemical formula 21] Ni x21 M 21 y21 M 22 1-x21-y21 (OH) 2 In the above formula 21, 0.3≦x21≦1, 0≦y21≦0.7, and M 21 and M. 22 are each independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr; [Chemical formula 31] Ni x31 Co y31 M 31 1-x31-y31 (OH) 2 In the above formula 31, 0.6≦x31≦1, and 0≦y31≦0.15; M 31 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
12. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the first heat treatment is carried out at a temperature in the range of 600° C. to 900° C. for 5 hours to 20 hours.
13. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the second heat treatment is carried out at a temperature in the range of 800° C. to 1100° C. for 5 hours to 20 hours.
14. 11. The method of claim 10, wherein preparing the second nickel-based oxide comprises mixing the second nickel-based hydroxide and a lithium raw material, subjecting the mixture to a second heat treatment, and pulverizing the resulting mixture to obtain the second nickel-based oxide in a single particle form.
15. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the first nickel-based oxide and the second nickel-based oxide are mixed so that a weight ratio of the first nickel-based oxide to the second nickel-based oxide is 9:1 to 5:
5.
16. 11. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the first nickel-based oxide, the second nickel-based oxide, and the cobalt compound are mixed such that the amount of cobalt contained in the cobalt compound is 0.01 to 7 parts by mol when the total amount of metals excluding lithium in the first nickel-based oxide and the second nickel-based oxide is 100 parts by mol.
17. The method of claim 10, wherein the first nickel-based oxide, the second nickel-based oxide, and the cobalt compound are mixed together with a lithium raw material.
18. The method for producing a positive electrode active material for a lithium secondary battery according to claim 17, wherein the lithium raw material is mixed in an amount of 1 to 4 parts by mol with respect to 1 part by mol of the cobalt compound.
19. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the third heat treatment is carried out at a temperature in the range of 650° C. to 900° C. for 5 hours to 30 hours.
20. A lithium secondary battery comprising a positive electrode containing the positive electrode active material according to any one of claims 1 to 9, a negative electrode, and an electrolyte.
Citation Information
Patent Citations
Positive electrode material and preparation method therefor, positive electrode plate and lithium ion battery
CN107681123A
Cathode active material, method of producing the same, and cathode and lithium secondary battery employing the same
JP2015018803A
Positive electrode active material for lithium secondary battery and lithium secondary battery including the same
JP2020077611A
Positive electrode active material for secondary battery, method for producing the same, and secondary battery including the same
JP2020504415A
Composite positive electrode active material, positive electrode including the same, lithium battery, and manufacturing method for the same
JP2021190431A